The Association Between STX1B Polymorphisms and Treatment Response in Patients With Epilepsy - Wang, Shitao; Zhou, Liang; He, Chenglu; Wang, Dan; Cai, Xuemei; Yu, Yanying; Chen, Liling; Lu, Di; Bian, Ligong; Du, Sunbing; Wu, Qian; Han, Yanbing (Frontiers in Pharmacology, 2021)
Background: Epilepsy is a debilitating brain disease with complex inheritance and frequent treatment resistance. Synaptic dysfunctions are associated with a myriad of neurological disorders, including epilepsy. However, the role of STX1B single nucleotide polymorphisms(SNPs) in epilepsy treatment remains unknown. Objective: This study aimed to explore the genetic association of STX1B SNPs with treatment response in patients with epilepsy in a Han Chinese population. Methods: We first examined the associations between STX1B SNPs and epilepsy in 1000 Han Chinese and the associations between STX1B SNPs and drug-resistant epilepsy in 450 subjects. Expression quantitative trait loci analysis was then conducted using 16 drug-resistant epileptic brain tissue samples and and results from the BrainCloud database (http://eqtl.brainseq.org). Results:The allelic frequencies of rs140820592 were different between the epilepsy and control groups(p=0.002) after Bonferroni correction. The rs140820592 was associated with significantly lower epilepsy risk among 1,000 subjects in the dominant model after adjusting for gender and age and Bonferroni correction (OR=0.542, 95%CI=0.358‒0.819, P=0.004). The rs140820592 also conferred significantly lower risk of drug-resistant epilepsy among 450 subjects using the same dominant model after adjusting for gender and age and Bonferroni correction (OR=0.260, 95%CI=0.103-0.653, P=0.004). Expression quantitative trait loci analysis revealed that rs140820592 was associated with STX1B expression level in drug-resistant epileptic brain tissues (p = 0.012), and this result was further verified in the BrainCloud database (http://eqtl.brainseq.org) (p = 2.3214×10-5). Conclusion: The STX1B rs140820592 may influence the risks of epilepsy and drug-resistant epilepsy by regulating STX1B expression in brain tissues.